Sosialisasi Stop Bullying dan Penyalahgunaan Narkoba di SMP IT Daarul Uzma Kecamatan Picung Kabupaten Pandeglang - Wahyuningrum, Rina; Putri, Putri; Humaemah, Ratu; Aini, Faridatul; Syafitri, Viyonisa Nabilah; Almunir, Rizal Rizqi (TAFANI: Jurnal Pengabdian Masyarakat, 2025)
In the era of globalization, social issues such as bullying and drug abuse have become increasingly complex and require serious attention. The educational activity themed “Stop Bullying and Drug Abuse Prevention” conducted by the KKN Group 42 of UIN Sultan Maulana Hasanuddin Banten in collaboration with the Picung Police at SMPIT Daarul Uzma aimed to raise student awareness about the dangers of these behaviors. The methods used included lectures, discussions, and interactive Q&A sessions. The results of this activity showed that students became more aware of the signs and impacts of both bullying and drug abuse. The event also successfully provided moral support to students to avoid negative behaviors, as reflected in the signing of a banner as a commitment. The collaboration between students, police, and the school proved effective in creating a safer and healthier environment and is expected to serve as a model for similar efforts in other schools.